2022
DOI: 10.1177/02683555211069772
|View full text |Cite
|
Sign up to set email alerts
|

Totally implantable venous access ports: A systematic review and meta-analysis comparing subclavian and internal jugular vein punctures

Abstract: Background Totally implantable venous access port (TIVAP) is a completely closed intravenous infusion system that stays in the human body for a long time. It is used for the infusion of strong irritating or hyperosmotic drugs, nutritional support treatment, blood transfusion and blood specimen collection, and other purposes. There are two common ways of TIVAP: internal jugular vein implantation and subclavian vein implantation. However, the postoperative complications of the two implantation methods are quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The internal jugular vein is close to the oropharynx and respiratory tract and has a high rate of catheter infection and thrombosis, which limits its clinical application. The infection rate of subclavian vein catheter is low, which is convenient for nursing, but the incidence of puncture complications is high, which is easy to cause pneumothorax, and accidental artery puncture cannot stop bleeding, so the technical requirements for the operator are higher [ 11 ]. Femoral vein puncture and catheterization will not cause serious life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal jugular vein is close to the oropharynx and respiratory tract and has a high rate of catheter infection and thrombosis, which limits its clinical application. The infection rate of subclavian vein catheter is low, which is convenient for nursing, but the incidence of puncture complications is high, which is easy to cause pneumothorax, and accidental artery puncture cannot stop bleeding, so the technical requirements for the operator are higher [ 11 ]. Femoral vein puncture and catheterization will not cause serious life-threatening complications.…”
Section: Discussionmentioning
confidence: 99%
“…Axillary vein catheterization is guided by real-time ultrasound. Studies have reported that axillary vein catheterization often passes through the pectoralis minor muscle, resulting in obvious traction discomfort when patients move their arms [ 11 ]. The risk of thrombosis in axillary vein catheterization is higher.…”
Section: Discussionmentioning
confidence: 99%
“…14,22,23 It should be noted that randomized trials comparing subcutaneous implantable port insertion via IJ and subclavian vein routes show equal rates of stenotic complications. [24][25][26] The number of previous catheterizations is potentially better correlated with CVS risk than site selection; the odds of CVS increase by 38% for each subsequent HD catheter placed. 27 The risk of catheter-related infection is the lowest with subclavian central venous catheters; the incidence of catheter-related bacteremia for subclavian lines is roughly half that of IJ lines.…”
Section: Who Should Insert the Catheter?mentioning
confidence: 99%
“… 14 22 23 It should be noted that randomized trials comparing subcutaneous implantable port insertion via IJ and subclavian vein routes show equal rates of stenotic complications. 24 25 26 The number of previous catheterizations is potentially better correlated with CVS risk than site selection; the odds of CVS increase by 38% for each subsequent HD catheter placed. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Implanted Venous Access Port (IVAP) as the latest infusion pathway solves the above problems. It is mainly used in cancer patients (4)(5)(6). The port is a closed venous infusion system with a port body attached to a central venous catheter under the skin.…”
Section: Introductionmentioning
confidence: 99%